Mastery, Modality, and Tsotsil Coexpressivity - John B. Haviland (Languages)
“Coexpressivity” is the property of utterances that marshal multiple linguistic elements and modalities simultaneously to perform the distinct linguistic functions of Jakobson’s classic analysis (1960). This study draws on a longitudinal corpus of natural conversation recorded over six decades with an accomplished “master speaker” of Tsotsil (Mayan), adept at using his language to manage different aspects of social life. The research aims to elaborate the notion of coexpressivity through detailed examples drawn from a range of circumstances. It begins with codified emic speech genres linked to prayer and formal declamation and then ranges through conversational narratives to gossip-laden multiparty interaction, to emphasize coexpressive connections between speech as text and concurrent gesture, gaze, and posture among interlocutors; audible modalities such as sound symbolism, pitch, and speech rate; and finally, specific morphological characteristics and the multifunctional effects of lexical choices themselves. The study thus explores how multiple functions may, in principle, be coexpressed simultaneously or contemporaneously in individual utterances if one takes this range of modalities and expressive resources into account. The notion of “master speaker” relates to coexpressive virtuosity by linking the resources available in speech, body, and interactive environments to accomplishing a wide range of social ends, perhaps with a special flourish although not excluded from humbler, plainer talk.